Deliberative Digital Twins for Reforming Participatory Planning in Indonesia: A Smart Governance Framework - Aulia, Fahmi (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2026)
The Development Planning Deliberation (Musrenbang) is a pillar of participatory democracy in Indonesia that has systematically failed to fulfill its deliberative mandate. The objective of this study is to propose and critically examine a “Deliberative Digital Twin” as a second-wave socio-technical intervention. Unlike previous digitalization efforts (e-Musrenbang) that merely digitized existing bureaucratic flows, this model integrates Urban Digital Twin (UDT) with System Dynamics (SD) and Agent-Based Modeling (ABM) to create a transparent policy evaluation ecosystem. Specifically, this framework aims to disrupt the political deadlock between the technocratic planning body (Bappeda) and the political interest of the legislature (DPRD) by arming non-expert citizens with evidence-based policy impact simulations. We present a multi-layered conceptual architecture for this model and provide a critical anticipatory analysis of implementation barriers, including institutional inertia and national data infrastructure challenges. We conclude that while high-risk, the Deliberative Digital Twin offers a new paradigm for shifting Musrenbang from a ritualistic procedure to an authentic, evidence-based participatory governance mechanism.